Penguatan Manajemen Data Kesehatan Anak dan Pendidikan Gizi Berbasis Sistem Rekam Medis di General Santos, Filipina - K. Prihartono Aksan Halim; Santy Christinawati; Sani Fitriyani; Siti Insani; Candra Mecca Sufyana (PADMA, 2025)
Child health remains a global concern, particularly in developing regions where data management and nutrition awareness are still limited. This international community service program aims to strengthen child health data management and improve nutrition education based on medical record systems in General Santos. The program was conducted by Politeknik Piksi Ganesha involving healthcare workers and community participants. The methods included training, system implementation, and educational outreach. A total of 20 participants were involved in the program. The results showed improvements in data accuracy, reduction of duplicate records, and increased participant understanding of child nutrition and data management. This initiative contributes to enhancing healthcare service quality and promoting better child health outcomes through integrated data and education approaches.